Embryonic development of hybrids of Pseudoplatystoma metaense Suarez, 2007 x Leiarius marmoratus Gill, 1870 (Siluriformes: Pimelodidae) (Orinoquia, 2016)
Embryonic development in fish is important for understanding their biology and systematics, through aspects such as morphology, growth, feeding, behavior and mortality. The objective of this work was the description of embryonic development of hybrids produced from crossing female Pseudoplatystoma metaense x male Leiarius marmoratus. Reproduction was induced in sexually mature broodstock using carp pituitary extract. The semined eggs were incubated in artisanal systems upflow of 70 l, making water changes by 20% every three hours with average temperature 26.2 ± 0.5ºC. Samples were taken at time intervals 0.25, 0.50, 1 and 2 hours post fertilization (hpf) and were fixed in 10% buffered formalin. Subsequently they observed and photographic records were taken. stage zygote and cleavage hpf 1 to 0:25, 2 at 0:50 cleaving, cleaving 3 and 4 to 0:75, cleaving 5 and 6 to 1:00, blastula (initial subdivision, was observed early and late) they were observed from 1:50 to 5:00 hpf, gastrula and closing at 6:00 blastoporo hpf, segmentation of somites from 10:00 to 17:00 hpf finally presenting hatching at 18:00 hpf. We conclude that the events of embryonic development of P. metaense x L. marmoratus are asynchronous, featuring a 30% fertility.
Keywords: embryogenesis; hybrid; egg; larva; artificial reproduction